Penguatan Profil Pelajar Rahmatan Lil ‘Alamin Melalui Kurikulum Pendidikan Agama Islam Di Mtss Darul Ma’rifah Desa Ulee Nyeue Kecamatan Banda Baro Kabupaten Aceh Utara - Tajussubki Tajussubki (Journal of Islamic Education and Law, 2026)
This study is motivated by the importance of strengthening students’ character in madrasah education through the values of the Rahmatan lil ‘Alamin Student Profile, particularly in response to educational developments that require a balance between knowledge, spirituality, morality, and social awareness. The Islamic Religious Education curriculum holds a strategic position because it functions not only as an instructional framework but also as a medium for fostering faith, noble character, moderation, responsibility, and social attitudes among students. The purpose of this study is to analyze the strengthening of the Rahmatan lil ‘Alamin Student Profile through the Islamic Religious Education curriculum at MTsS Darul Ma’rifah, Ulee Nyeue Village, Banda Baro District, North Aceh Regency. This research employed a qualitative approach with a field study design. The research subjects included the head of the madrasah, Islamic Religious Education teachers, the vice principal for curriculum affairs, and students. Data were collected through interviews, observation, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The results show that the strengthening of the Rahmatan lil ‘Alamin Student Profile is carried out through the integration of religious values, noble character, moderation, responsibility, independence, and social concern in Islamic Religious Education learning, religious habituation, teacher role modeling, and madrasah culture. Islamic Religious Education teachers play an important role in connecting learning materials with students’ daily lives, so these values are not limited to theoretical understanding but are reflected in actual behavior. The study concludes that the Islamic Religious Education curriculum can serve as a strategic instrument in shaping students who are religious, moderate, moral, integrated, and socially aware. The contribution of this study lies in explaining that strengthening the Rahmatan lil ‘Alamin Student Profile should be implemented integratively through curriculum, learning practices, habituation, teacher role modeling, and madrasah culture.